Monitoring of lower limb comfort and injury in elite football - Kinchington, M.; Ball, K.; Naughton, G. (Journal of Sports Science & Medicine, 2010)
The aim of the study was to examine the relation between lower limb comfort scores and injury and to measure the responsiveness of a lower limb comfort index (LLCI) to changes over time, in a cohort of professional footballers. Lower limb comfort was recorded for each individual using a comfort index which assessed the comfort status of five anatomical segments and footwear. Specifically we tested the extent to which comfort zones as measured by the LLCI were related to injury measured as time loss events. The hypothesis for the study was that poor lower limb comfort is related to time loss events (training or match day). A total of 3524 player weeks of data was collected from 182 professional athletes encompassing three codes of football (Australian Rules, Rugby league, Rugby Union). The study was conducted during football competition periods for the respective football leagues and included a period of pre- season training. The results of regression indicated that poor lower limb comfort was highly correlated to injury (R2 =0.77) and accounted for 43.5 time loss events/ 1000hrs football exposure. While poor comfort was predictive of injury 47% of all time loss events it was not statistically relevant (R2 =0.18). The results indicate lower limb comfort can be used to assess the well-being of the lower limb; poor comfort is associated with injury, and the LLCI has good face validity and high criterion-related validity for the relationship between comfort and injury.